Vijftig Internationale Kunstenaars. (Kessel : Galerij Dobbelhoef, 1979)
Adami ; Art, Raymond ; Bertrand, Gaston ; Bogart, Bram ; Charchoune ; Cobbaert, Jan ; Corneille ; Delahaut, Jo ; Delaunay, Sonia ; Degottex, Jean ; Delmotte ; de St. Phalle, Niki ; Delvaux, Paul ; Domela ; Dries, Jan ; Fautrier ; Folon, Michel ; Guiette, René ; Hendrickx, Jos ; Hoenraet, Luc ; Ivens, Renaat ; Joostens, Paul ; Kiemeneij, Jan ; Lacasse, Jozef ; Lam, Wifredo ; Lanskoy ; Lindström ; Lismonde ; Magnelli ; Martin, Philip ; Matta ; Mesens, E.L.T. ; Miro, Joan ; Nellens, Roger ; Neve, Jacques ; Pedersen, Carl-Henning ; Peire, Luc ; Raveel, Roger ; Recalcati ; Reychier, Rita ; Richter, Konrad ; Rooskens ; Steyaert, Elsa ; Survage ; Swimberghe, Gilbert ; Van den Berghe, Frits ; Van der Cam, Serge ; Van Hecke, Willem ; Van Severen, Dan ; Van Velde, Geer ; Velikovic ; Vets, Jef ; Wegner, Erick, Wesselman, Tom ; Zao, Wou ki
Vijftig Internationale Kunstenaars, Galerij Dobbelhoef, Kessel, 19 mei - 15 juli 1979
boek